1987
DOI: 10.1007/bf02011247
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cell size and viability of soil bacteria

Abstract: The number of bacterial cells in soil that form colonies on nutrient agar represent a small fraction of the direct microscopic counts (DMC). The colony-forming cells have larger cell dimensions than the very small ("dwarf") cells which represent the majority of the DMC. This may indicate that the dwarf cells are species unable to form visible colonies on agar, or that they swell to normal dimensions when growing. Indigenous bacterial cells were separated from soil by density gradient centrifugation and fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
65
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(72 citation statements)
references
References 19 publications
5
65
2
Order By: Relevance
“…Further work using a similar approach showed that the growth rate (activity) of the larger cells (Ͼ0.25-m 3 biovolume) was higher than that of the smaller-volume cells in seawater samples, demonstrating that cell size is an issue (34). This issue has also been raised for soil bacteria (2).…”
mentioning
confidence: 93%
“…Further work using a similar approach showed that the growth rate (activity) of the larger cells (Ͼ0.25-m 3 biovolume) was higher than that of the smaller-volume cells in seawater samples, demonstrating that cell size is an issue (34). This issue has also been raised for soil bacteria (2).…”
mentioning
confidence: 93%
“…Previous investigations already indicated that a large fraction of environmental microbial communities A. FELSKE a n d OTHERS is in a stage of low activity or resting (Bakken & Olsen, 1987;Roszak et af., 1984). DNA obtained from environmental samples could thus originate from such dormant cells, from dead cells (Josephson et al, 1993), or even from free DNA.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that there are positive correlations between activity and cell size (3), cell size and culturability (1,2), and activity and culturability (33). Thus, while they may carry a large proportion of the genetic material, the numerically dominant component of soil bacterial communities (consisting of very small cells [15]) does not contribute greatly to biomass or metabolic activity (1).…”
mentioning
confidence: 99%